Time-varying oscillation detector based on improved LMD and robust Lempel–Ziv complexity. (June 2016) - Xie, Lei; Lang, Xun; Chen, Junghui; Horch, Alexander; Su, Hongye
Abstract: A novel method based on improved local mean decomposition (LMD) for oscillation detection is proposed. Due to its capability to analyze amplitude and frequency modulated signals, LMD is especially suitable for characterizing time-varying control loop oscillations. In contrast to empirical mode decomposition (EMD), the improved LMD performs better in the following aspects: (i) ability to extract both single/multiple oscillations in process output, (ii) robustness to noise, and (iii) capability to handle non-stationary trends. In addition, improved LMD can precisely characterize the time-varying oscillations without distortion and frequency leakage even for short time series. Finally, a robust Lempel–Ziv complexity based statistic for time-varying oscillation detection is presented. Simulation examples and industrial applications are provided to demonstrate the effectiveness of the proposed LMD oscillation detector. Abstract : Highlights: A detector is proposed for non-stationary, nonlinear and multiple oscillations. The detector promptly extracts oscillations in short-time series and it is robust to random disturbances. The proposed robust Lempel–Ziv complexity based statistic is particularly applicable for time-variant oscillation detection.